2014
DOI: 10.14740/jnr271w
|View full text |Cite
|
Sign up to set email alerts
|

Prognostication of Electrocardiographic Changes With Status Epilepticus in African American Population

Abstract: Background: Status epilepticus (SE) is a medical emergency and requires rapid diagnosis and treatment to reduce morbidity and mortality. The general approach to management and treatment of SE is largely unexplored and it remains unclear if other factors besides age and etiology represent independent outcome predictors for SE. There have been previous studies that document changing electrocardiogram (ECG) tracing through SE and following the termination of SE, indicating a dynamic, pathological response of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 15 publications
(31 reference statements)
1
6
0
Order By: Relevance
“…In the present study, cardiac arrhythmias occurred in 15 patients (20.3%). El Amrousy et al [30] and Kurukumbi et al [9] reported similar results in both children and adults. Activated sympathetic tone causes damage to cardiac myofilaments and arrhythmogenic changes in cardiac electrical activity, as well as an increased risk of ventricular arrhythmias [31].…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…In the present study, cardiac arrhythmias occurred in 15 patients (20.3%). El Amrousy et al [30] and Kurukumbi et al [9] reported similar results in both children and adults. Activated sympathetic tone causes damage to cardiac myofilaments and arrhythmogenic changes in cardiac electrical activity, as well as an increased risk of ventricular arrhythmias [31].…”
Section: Discussionmentioning
confidence: 69%
“…Lethal cardiac arrhythmias with or without gross structural cardiac damage are one possible mechanism leading to death following SE [ 38 ]. In an animal model of SE, myocardial ischemia and sympathetic over-stimulation cause modest damage to cardiac myofilaments, resulting in electrical alterations in heart function and an increased risk of fatal arrhythmias [ 31 ]; Kurukumbi et al [ 9 ] reported that all deaths due to CSE had ECG abnormalities; therefore, strict monitoring of cardiac function is critical in the management of SE. Furthermore, seizure-related cardiac dysfunction is thought to be an important pathophysiological mechanism in sudden cardiac death [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proportions of ST-segment shift that we found are globally higher than those reported in other studies. Boggs et al (25) and Kurukumbi et al (27) identified ST-segment elevation in 3.3% and 3.5%, and ST-segment depression in 10.0% and 8.8%, respectively. Only in the Hocker et al (26) study population was ST-segment elevation and depression found in 11.4% and 5.7% of patients.…”
Section: Discussionmentioning
confidence: 98%
“…The authors reported a rate of ECG abnormality of 65.7% (23/35 patients) (26). Finally, Kurukumbi et al (27) found a rate of ECG abnormalities in 84% of patients with SE, in a population composed of patients of African-American origin, greater than 75% of whom were known to have epilepsy. In rare cases, the occurrence of cardiorespiratory arrest in direct relation to asystole induced by SE has also been reported (28, 29).…”
Section: Discussionmentioning
confidence: 98%